Tingkat Kepuasan Pasien di Poli Gigi Puskesmas Padangsari Kecamatan Banyumanik Kota Semarang - Melly Presilia; Respati Wulandari; Eni Mahawati (Universitas Pahlawan Tuanku Tambusai, 2026)
Puskesmas Padangsari, as one of the primary healthcare institutions, strives to provide services that meet the expectations of the community while also supporting the overall improvement of public health. All forms of optimal dental health services aim to meet the needs and expectations of patient satisfaction. The quality of service can be viewed as a parameter that reflects the interaction and relationship between consumer expectations and the performance results of the service provided.This research aims to determine the level of patient satisfaction at Puskesmas Padangsari. A total of 247 patients filled out the satisfaction questionnaire, and the results showed that 185 patients were very satisfied with the dental clinic service, 57 patients were satisfied, and 5 patients were less satisfied with the service provided at the dental clinic of Puskesmas Padangsari.